"Caracterizacion morfo-estructural y faneroptica del cerdo negro criollo en la Provincia de Manabi". - Luque Murillo, Bayron Gabriel (2015)
The research was carried out in the province of Manabí in the coastal region, with a 03' 08'' 1 Territorial location south latitude and 80 degrees west longitude 27'02'' at an elevation of 6-350 meters, assuming a temperature of 25 ° C and rainfall of 200-1500 mm annually. Practical work began on July 8, two thousand fifteen ended October 2, two thousand fifteen a stay of 86 Creole pig in the province of Manabí and establish the morpho-structural characteristics of black Creole pig in the province of Manabí. In the fieldwork he was fulfilled producers visiting the different places of the province of Manabí, finding 106 females and 57 males with an average of 37.98 and 46.02 kg of live weight. The corporal variables measured were: head length (LZC), head width (LZA), snout length (LH), width (AH), rump length (LGR), croup width (AGR), Height to cross (ALC), croup height (ALG), tail birth Height (ANC), longitudinal diameter (DL), dorsoesternal Diameter (DDE), bicostal Diameter (DBC), thoracic perimeter (PTO), Perimeter Reed (PCA), ear length (LO), ear width (AO). Cephalic (CFI), proportionality (PDI), corporal (CPI), pelvic (PVI), chest (ITO) on chest depth (PRP), toraxic pastern (IMT): zoometric these variables, the following indices were calculated zoometric. Descriptive statistics and analysis of variance for the variables and indices zoometric having the effect of sex was made. Averages (cm) and the corporal variables were: females (LZC), 28.43; (LZA), 13.63; (LH), 17.96; (AH), 8.95; (LGR), 27.52; (AGR), 22.10; (ALC), 61.70; (ALG), 67.75; (ANC), 53.40; (DL), 78.53; (DDE), 36.59; (DBC), 23.14; (PTO), 93.72; (PCA), 14.78; (LO), 18.97; (AO), 17,31 and in males (LZC), 28.13; (LZA), 15.60; (LH), 17.93; (AH), 10.71; (LGR), 29.06; (AGR), 21.46; (ALC), 62.25; (ALG), 68.08; (ANC), 53.01; (DL), 78.66; (DDE), 35.98; (DBC), 24.08; (PTO), 94.32; (PCA), 14.98; (LO), 19.08; (AO), 17,04 in these variables no significant differences (P <0.01) were found. The values (%) indices calculated in females and males were: ICF, 47.97 and 55.49; IPD, 78.57 and 79.14; ICP, 83.80 and 83.41; IPV, 80.30 and 73.93; ITO, 63.37 and 66.93; PRP, 58.59 and 57.81; IMT, 15.65 and 15.88. Faneropticas characteristics in the absence of excelled mamellas with